2020
DOI: 10.1101/2020.01.04.894865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

1-[(4-Nitrophenyl)sulfonyl]-4-phenylpiperazine Treatment After Brain Irradiation Preserves Cognitive Function in Mice

Abstract: AbstractBackgroundNormal tissue toxicity to the CNS is an inevitable consequence of a successful radiotherapy of brain tumors or cancer metastases to the CNS. Cranial irradiation commonly leads to neurocognitive deficits that manifest months or years after treatment. Mechanistically, radiation-induced loss of neural stem/progenitor cells, neuro-inflammation and de-myelinization are contributing factors that lead to progressive cognit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…However, the number of EGFP + NSPCs in Passage #2 neurospheres from individual animals of the same sex varied and none of the observed differential effects of DRAs between sexes reached the level of statistical significance (Figure 1C) . In agreement with our previous report (15), radiation predominately eliminated the Nestin-EGFP high population of cells from neurospheres, consistent with the known exquisite radiation sensitivity of neural stem cells. The differences between sexes in the total number of EGFP + cells in response to individual DRAs became smaller with increasing radiation doses in alignment with the generally non-sex-specific cell killing effects of ionizing radiation (Figure 1D/E) .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the number of EGFP + NSPCs in Passage #2 neurospheres from individual animals of the same sex varied and none of the observed differential effects of DRAs between sexes reached the level of statistical significance (Figure 1C) . In agreement with our previous report (15), radiation predominately eliminated the Nestin-EGFP high population of cells from neurospheres, consistent with the known exquisite radiation sensitivity of neural stem cells. The differences between sexes in the total number of EGFP + cells in response to individual DRAs became smaller with increasing radiation doses in alignment with the generally non-sex-specific cell killing effects of ionizing radiation (Figure 1D/E) .…”
Section: Resultssupporting
confidence: 93%
“…Nestin-EGFP + NSPCs were harvested from both male and female newborn pups and cultured as neurospheres. We have previously reported that Nestin promoter driven EGFP expression in this mouse strain is correlated with self-renewal capacity (15). Passage #2 neurospheres were pretreated with DRAs at 1 μM concentrations, irradiated with 0, 2 or 4 Gy and cultured for 2 weeks during which DRAs were added 3x/week (Figure 1A) .…”
Section: Resultsmentioning
confidence: 93%
“…Anti-TNF-a treatment, for example, reduced acute brain pathology after 20-Gy cranial radiation in a mouse model (Wilson et al, 2009). In a more recent study, a compound identified through a high-throughput screen was shown to decrease IL-6 expression and correspondingly reduce GFAP and Iba1 labeling (for astrocytes and microglia respectively) following cranial radiation in a mouse model (10 Gy at 8 weeks); treated mice also showed improved performance on tests of novel object and object-in-place recognition and fear conditioning (Bhat et al, 2020). Since multiple cytokines appear to be involved in neuroinflammation, broad spectrum anti-inflammatory treatments represent an attractive intervention option.…”
Section: Modulation Of Inflammation and Immune Responsementioning
confidence: 98%